Estimation of ETo with Hargreaves-Samani and FAO-PM temperature methods for a wide range of climates in Iran - Raziei, Tayeb (2013)
Monthly data records of 40 Iranian stations distributed over the country, for the period 1971–2005, were utilized for estimation of reference evapotranspiration (ETo) using Penman–Monteith (PM-ETo), Hargreaves–Samani (HS) and FAO-PM temperature (PMT) methods. To estimate ETo with HS and PMT methods, appropriate kRs, an empirical radiation adjustment coefficient, were considered for each station, whereas Tmin was adjusted for estimation of Tdew and used only for PMT computation. It was found that the appropriate kRs for both HS and PMT methods are identical for a given station and it is generally smaller in sub-humid and humid than in semi-arid to hyper-arid climates. The performance of the PMT was further improved in both arid and humid climates when Tmin was adjusted. The result suggested that the HS and PMT methods appropriately predict ETo for all climatic regions of Iran if the appropriate kRs was utilized. However, the considered methods showed weak performances for some stations in arid and hyper-arid climates of eastern and southern Iran owing to the effect of extreme and variable wind speed inherent in the PM-ETo. Thus, the role played by wind speed in ETo estimation was examined; the result indicated that the existence of extreme winds, and also the time variability of wind speed, is responsible for the observed discrepancies between PMT and PM-ETo estimates. The spatial patterns of ETo computed with HS and PMT methods found to be identical and resemble to that of PM-ETo, all showing a gradual increasing from north to south, with the lowest ETo values observed over northern humid and sub-humid climates of Iran and larger ETo for arid and hyper-arid climates in the southern and eastern country. Results indicated that the HS and PMT methods are appropriate alternatives for estimation of ETo for all climatic regions of Iran